The Symbol of Mother in The Work Of "Dunyoning Ishlari" By Utkir Khoshimov - Muzaffarova N.L (Academia One Publishing, 2023)
This article is devoted to the analysis of the symbol of "mother" in Utkir Khoshimov's work "Dunyoning ishlari", and how the writer approached the image of "mother" within this work is discussed. We know that the writer is one of the famous writers of the Uzbek people with his works. His work is widely analyzed and studied in Uzbek literature. The writer wrote stories with the image of "mother" in his work "Dunyoning ishlari" and covered this topic in more detail. In this article, these stories are analyzed as the main source.
Keywords: Symbol; Symbolism; Society; Relationship